Electribius relictus, a new extant species of Artematopodidae (Coleoptera: Elateroidea) from Veracruz, Mexico - Arriaga-Varela, Emmanuel; Escobar, Federico (Zootaxa, 2014)
Electribius relictus sp. nov. (Artematopodidae) is described from a cloud forest fragment in central Veracruz, Mexico. This species is distinguished from the other extant species known, E. crowsoni Lawrence (Mexico) and E. similis Lawrence (El Salvador), by the pronotum and elytra completely black, pronotum with margins crenulate at base, fifth abdominal ventrite with distinct median ridge, and the shape of aedeagus. The new species is illustrated and a key for the identification of extant species of the genus and ecological data for the collecting site are provided.